2020
DOI: 10.12659/msm.921087
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Karyopherin Subunit alpha 2 (KPNA2) Predicts Unfavorable Prognosis and Promotes Bladder Cancer Tumorigenicity via the P53 Pathway

Abstract: Departmental sources Background: We sought to investigate the expression of KPNA2 in bladder cancer (BC) and its relationship with prognosis, and to analyze the potential mechanism of KPNA2 in promoting BC progression. Material/Methods: The RNA-seq data on BC from The Cancer Genome Atlas (TCGA) database were imported into R statistical software for differential analysis. The clinical data for patients with BC were screened and analyzed with R software. The survival curve was drawn with the Kaplan-Meier Plotter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This outcome could be influenced by different data processing or updated survival information. Thus, we further used, OncoLnc (http://www.oncolnc.org/) and the Kaplan Meier plotter method (27,28) to further update and analyze these data, the final results were consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 75%
“…This outcome could be influenced by different data processing or updated survival information. Thus, we further used, OncoLnc (http://www.oncolnc.org/) and the Kaplan Meier plotter method (27,28) to further update and analyze these data, the final results were consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 75%
“…Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of these genes in DAVID showed that the involvement of KPNA2 in HCC progression was associated with p53 signaling pathway ( Figure 7a ). KPNA2 has been reported to play a tumor-promoting action in several human cancers via inactivation of p53 signaling [ 23 , 24 ]. Here, we explored whether miR-26b-5p could regulate p53 signaling by targeting KPNA2.…”
Section: Resultsmentioning
confidence: 99%
“…FGF1 has been shown to inhibit p53‐dependent apoptosis and arrest cell growth 36,37 . The P53 signaling pathway plays a crucial role in tumorigenesis, as it modulates key cellular functions such as DNA damage repair, cell cycle progression, and apoptosis 38–40 …”
Section: Discussionmentioning
confidence: 99%